2016
DOI: 10.1186/s12889-016-3570-3
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary bout durations and metabolic syndrome among working adults: a prospective cohort study

Abstract: BackgroundThis study aimed to examine the associations between time spent in prolonged and non-prolonged sedentary bouts and the development of metabolic syndrome.MethodsWe used data from a prospective study of Japanese workers. Baseline examination was conducted between 2010 and 2011. A total of 430 office workers (58 women) aged 40-64 years without metabolic syndrome were followed up by annual health checkups until 2014. Metabolic syndrome was defined as having ≥ 3 out of 5 diagnostic criteria from the Joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 35 publications
0
68
1
3
Order By: Relevance
“…Of the prospective studies identified, two used heart rate FLEX to measure sedentary time , with the remaining studies employing accelerometry . Follow‐up periods ranged from 2 to 5.8 years, with sample sizes ranging from 376 to 2,027 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Of the prospective studies identified, two used heart rate FLEX to measure sedentary time , with the remaining studies employing accelerometry . Follow‐up periods ranged from 2 to 5.8 years, with sample sizes ranging from 376 to 2,027 participants.…”
Section: Resultsmentioning
confidence: 99%
“…Diversos estudios han reportado los efectos negativos del comportamiento sedentario sobre la salud, condición que ha surgido como un factor de riesgo potencial e independiente de los niveles de actividad física que realiza un individuo 24,25 . En este estudio se determinó que 46,6% de la población chilena es altamente sedentaria, es decir, pasa gran parte de su tiempo sentada o recostada.…”
Section: Discussionunclassified
“…After reviewing their titles and abstracts, a total of 63 articles were excluded because of the following reasons: not reporting sedentary behavior (n = 22), special or patient populations (n = 16), incorporating children as subjects (n = 9), studies not conducted in Japan (n = 5), individual calibration or validation studies of wearable devices (n = 4), non-human subjects (n = 3), non-English articles (n = 2), and review or protocol articles (n = 2). The characteristics of the seven articles [22][23][24][25][26][27][28] that met the inclusion criteria are summarized in Table 2. Since this systematic review is based on a search done on a single database (the PubMed), caution should be observed in terms of comprehensiveness.…”
Section: A Systematic Review On Sedentary Behavior Assessments In Japanmentioning
confidence: 99%
“…Of the seven articles reviewed in this study, 6 adopted the waist-worn Active style Pro tri-axial accelerometer [22][23][24][25][26][27] . The remaining article reported on the thighworn activPAL to develop and test an occupational sitting questionnaire 28) .…”
Section: A Systematic Review On Sedentary Behavior Assessments In Japanmentioning
confidence: 99%